Intrathyroidal oxyphilic parathyroid carcinoma: A potential diagnostic caveat in cytology?. Issue 8 (26th May 2016) - Wong, Yin Ping; Sharifah, Noor Akmal; Tan, Geok Chin; Gill, Anthony James; Ali, Syed Z.
Abstract : Oxyphilic (oncocytic) parathyroid lesions are very uncommon and their cytological features are rarely described. Due to the similarities in anatomical location and indistinguishable cytomorphological features, these lesions are easily confused with neoplastic and non‐neoplastic thyroid lesions on fine needle aspiration (FNA). The diagnosis becomes more challenging in cases of unusual intrathyroidal location of the parathyroid lesions in the absence of clinical evidence of hyperparathyroidism, which simulate thyroid nodules clinically. We describe a case of intrathyroidal oxyphilic parathyroid carcinoma in a 66‐year‐old female, who presented with a dominant left "thyroid" nodule. FNA smears were cellular, comprising predominantly of oxyphilic cells arranged in papillary‐like architecture with occasional nuclear grooves, which was mistaken for oncocytic variant of papillary carcinoma of the thyroid. The histological diagnosis of oxyphilic parathyroid "adenoma" was made following total thyroidectomy. The tumor, unfortunately, recurred 7 years later with associated multiple lung metastases. When dealing with thyroid lesions comprising predominantly of oncocytic cells, one should consider oxyphilic parathyroid neoplasms as one of the differential diagnosis. In difficult equivocal cases, a panel of immunocytochemical stains (PTH, GATA3, TTF‐1, PAX8, and thyroglobulin) can be helpful. In addition, a combination of valuable clinical, radiological, and laboratory data, including serum calcium and parathyroid hormone levels are key to arriving at an accurate cytological diagnosis. Diagn. Cytopathol. 2016;44:688–692. © 2016 Wiley Periodicals, Inc.